THE INFLUENCE OF SATISFACTION AND RELATIONSHIP MARKETING ON LOYALTY WITH INDIVIDUAL CHARACTERISTICS AS A MODERATOR: A Case Study on Islamic Banking Customers in East Java - Arwani, Mokhamad; Suprehatin, Suprehatin (Journal of Indonesian Economy and Business, 2011)
Prospects to attract customers to the Islamic banks do not seem to be very promising. This is mainly due to the fact that customers who had joined conventional banks arereluctant to change their accounts to Islamic banks. Customer loyalty of Islamic banks has been considered relatively low (34%) as compared to that of conventional banks. The purpose of this paper is to analyze the influence of satisfaction and relationship marketing on loyalty. 112 eligible respondents of Islamic bank customers were collected using a designed questionnaire. Structural Equation Modeling (SEM) was employed in the analysis. Findings suggest that in the context of Islamic banks, personal characteristics have a direct impact on customer loyalty, and it does seem to be a moderating variable influence of satisfaction and relationship marketing to customer loyalty. Satisfaction does not directly affect loyalty, but it indirectly affects loyalty through relationship marketing.Keywords: customer satisfaction, relationship marketing, personal characteristics, loyalty, Islamic banks.